HUBUNGAN SELF-CARE DAN MOTIVASI DENGAN KUALITAS HIDUP PASIEN GAGAL JANTUNG - Adittia; Mustika Anggiane Putri (Fakultas Kedokteran Universitas Trisakti, 2024)
The quality of life, as defined by the World Health Organization, is more than just physical health; it encompasses psychological well-being, social relationships, and the environment around us. Self-care, life motivation, and quality of life are interdependent and closely related. Good self-care helps maintain the energy and health necessary to achieve life goals. Strong life motivation encourages individuals to take care of themselves to reach their goals, and both contribute to an improved overall quality of life. Heart failure can significantly reduce a patient's quality of life. However, self-care and life motivation can help control the condition, maintain body function, and improve overall quality of life. Good self-care can prevent recurrence and help keep the condition stable, while life motivation can make patients more enthusiastic and optimistic in facing their condition. With high motivation, patients tend to engage in more activities they enjoy, resulting in an improved quality of life. This study aims to evaluate the relationship between self-care, motivation, and quality of life in heart failure patients. The study involved 74 heart failure patients, and the Minnesota Living with Heart Failure Questionnaire was utilized to determine the quality of life. The Self-Care of Heart Failure Index was used to measure self-care ability, whereas a motivation questionnaire was used to assess their motivation. The study found a significant relationship between self-care (p=0.003) and motivation (p=0.045) with quality of life.